The critical success factors for the use of information systems and its impact on the organizational performance - Mulyani, S. (Medwell Journals, 2016)
This study examines that how much the influence of self-efficacy, personal attitude and subjective norms partially to AIS and the influence of AIS affected by self-efficacy, personal attitude and subjective norms to the organization's performance. This study uses descriptive analytic research method and SEM-PLS statistic method. Data is collected from questionnaire distributed and returned from the employees of Accounting Department on Government-Owned Company in Fertilizer Industry as respondent. The results indicate a positive influence of self-efficacy, personal attitude and subjective norms to information system and a positive influence of information system affected by self-efficacy, personal attitude and subjective norms to the organization performance. Â© Medwell Journals, 2016.